Spectroscopy of electric arc discharge plasma with admixtures of W, Mo, Cr - Lebid, A.V.; Veklich, A.N.; Tmenova, T.A. (Вопросы атомной науки и техники, 2016)
Plasma of electric arc discharges between composite Cu-W, Cu-Mo and Cu-Cr electrodes in argon flow and
their spectra were studied by optical emission spectroscopy. Since values of oscillator strengths for W I, Mo I and
Cr I presented in various databases are significantly different, selection of spectroscopic data for these elements
(particularly oscillator strength) was expected to be useful for plasma diagnostics. The Boltzmann plot method
was used as a tool for selection of appropriate spectral lines and their spectroscopic data. The main result of the
paper are lists of W I, Mo I and Cr I spectral lines and spectroscopic data, which can be recommended for
purposes of diagnostics of plasma with such metal impurities. Методами оптической эмиссионной спектроскопии исследована плазма электродугового разряда между
композитными Cu-W, Cu-Mo и Cu-Cr электродами. Поскольку значения сил осцилляторов для линий W I,
Mo I и Cr I, представленные в разных литературных источниках, существенно различаются, то считалось
целесообразным провести селекцию спектроскопических констант данных элементов, для чего
использовался метод диаграмм Больцмана. Основными результатами работы являются таблицы
спектральных линий W I, Mo I и Cr I, а также соответствующих спектроскопических данных,
рекомендованных для диагностики плазмы с примесями этих металлов. Методами оптичної емісійної спектроскопії досліджено плазму електродугового розряду між
композитними Cu-W, Cu-Mo та Cu-Cr електродами. Оскільки значення сил осциляторів для ліній W I, Mo I
та Cr I, які наведені у різних літературних джерелах, суттєво відрізняються, то вважалось за доцільне
провести селекцію спектроскопічних констант цих елементів, для чого використано метод діаграм
Больцмана. Основними результатами роботи є таблиці спектральних ліній W I, Mo I та Cr I, а також
відповідні спектроскопічні дані, які рекомендовані для діагностики плазми електродугового розряду з
домішками цих металів.